STRUCTURE AND ANALYSIS OF RAW BASIS OF NON-FERROUS METALS OF THE REPUBLIC OF BELARUS - G. V. Dovnar; A. A. Andrits; A. N. Stepanjuk (Литьë и металлургия)
Raw materials base of non-ferrous metals in the Republic of Belarus is analysed in this article.